The Application of Factor Analysis and Kernel Density Estimation Model in the Appraisal of Spatial Development of Tonekabon Rural Areas - Dr. Gharib Fazelniya; Masoud Rajaiee; Seyed Yaser Hakimdoost (جغرافیا و آمایش شهری منطقه‌ای, 2014)
in geographical studies of  rural areas ,  due to the diversity of place and space phenomenon, it is not possible to study as single  and individual. Therefore, the first step is to classify these phenomena in similar categories. In particular, factor analysis as a powerful tool against this problem, is responsible to develope solutions to reduce and analyze the factors . In this paper, 38 indicators were used for leveling villages of  Tonekabon city , which was reduced using factor analysis to four factors. Today, he use of geographic information systems in the spatial analysis of rural development and using statistical models  and tests of graphics benchmark in order to provide spatial data base, sorting, spatial display of information , the integration of spatial information and analysis is common. The research method  in this study is analytical-synthetic method  and the data analysis as qualitative and quantitative were made  using inferential statistical methods using SPSS and ArcGIS10 softwares. The results show that economic and physical factors, with special quantity of  17/305, is lonely able to calculate 33/769% of the variance  And has the most effect among the four factors and  is known as a major factor in leveling  the villages. Also the best model for estimating the density of development in the region, is kernel model which was  selected  as  the best model with determinant factor of 0.71. According to this model, the development density is in the villages of northwest part of the town.